Culture-Negative Streptococcus suis Infection Diagnosed by Metagenomic Next-Generation Sequencing - Yuanyuan Dai; Li Chen; Wenjiao Chang; Huaiwei Lu; Peng Cui; Xiaoling Ma (Frontiers Media S.A., 2019)
Background:Streptococcus suis is a zoonotic pathogen that can cause severe infections such as meningitis and septicemia in both swine and humans. Rapid and accurate identification of the causative agent is very important for guiding clinical choices in administering countermeasures.Case Report: Here, we report a case of fatal S. suis infection in a patient who worked as a butcher in China. The 59-year-old man, who had previously undergone splenectomy, injured his finger while processing pork and developed severe sepsis. While blood cultures were negative following antibiotic treatment, S. suis was determined to be the causative agent by metagenomic next-generation sequencing (mNGS) and Sanger sequencing.Conclusion: Identification of etiological agents using techniques such as blood culture prior to antibiotic treatment is very important. mNGS may represent a useful method for diagnosis of infectious diseases, especially post-antibiotic treatment.